Assessment of detection threshold and preference for sweet taste across ethnicities in university students - Abdul Manaf, Marina; Aziz, Nur Asyirah (Progress in Nutrition, 2025)
Background and aim: Individuals taste sensitivity for sweetness determines their taste preference to perceive sweet taste. The preference for sweetness varies according to gender and ethnicity. The objective of this study was to assess the detection threshold and preference for sweet taste among undergraduate students from Malay, Chinese, and Indian backgrounds.Methods: Ninety students aged between 19 and 27 years were selected as panelists for this study. The three-alternative forced choice (3-AFC) method was employed to determine the detection threshold for sweet taste in sucrose solutions. A 9-point hedonic scale was used to determine the sensory preference for sweet taste in a tea beverage.Results: The findings indicate no significant difference (p > 0.05) in the detection threshold for sweet taste among the three ethnicities. In terms of detection threshold ranking, Chinese students had the lowest detection threshold for sweet taste (8.25 mM), followed by Malay (9.78 mM) and Indian students (11.51 mM). In terms of sensory preference, Malay and Indian students preferred higher degree of sweet taste (219 mM) than Chinese students (73 mM). Conclusions: In general, there was no correlation (p > 0.05) between detection threshold and preference for sweet taste among university students of different ethnic groups in Malaysia.